The Mbuak Manten Tradition in Inter-Hamlet Marriages in Gadungan Village, Puncu District, Kediri Regency: A Perspective of Sahal Mahfudz’s Social Fiqh - Muham Muhammad Mubarok; Fakhruddin Fakhruddin; Ahmad Izzuddin; Naela Nuril Alfin (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2026)
The mbuak manten tradition in Gadungan Village serves as a customary solution to the inter-village marriage prohibition, which is culturally believed to bring misfortune (balak). Although this prohibition has no normative basis in Islamic law, it continues to persist and influence local marriage decisions. This study examines how the local wisdom embedded in the mbuak manten tradition can be understood within Islamic law, specifically through Sahal Mahfudz’s Social Fiqh perspective. The research aims to analyze the tradition’s relevance within the framework of social fiqh. Using a qualitative empirical approach, data were collected through interviews with customary leaders, religious figures, tradition practitioners, and community members, supported by documentation and literature review. The analysis applies Sahal Mahfudz’s social fiqh, which emphasizes the contextualization of Islamic law based on social welfare (maṣlaḥah). The findings indicate that the mbuak manten tradition represents a form of local social ijtihad, functioning as a negotiation mechanism between customary norms and Islamic principles. From the perspective of social fiqh, this tradition can be classified as ‘urf ṣaḥīḥ (valid custom) as long as it does not contradict fundamental Islamic law and remains oriented toward public welfare. This study enriches the discourse on Islamic law grounded in local wisdom by demonstrating that custom can serve as a social instrument to maintain order and harmony. The study recommends preserving local traditions through a continuous and critical reinterpretation process to ensure their alignment with Islamic values and the evolving needs of contemporary society.